PENGARUH KESESUAIAN JUMLAH PINJAMAN, PENINGKATAN OMZET USAHA DAN KESESUAIAN JANGKA WAKTU PENGEMBALIAN TERHADAP KELANCARAN KUR - Gwee, Lorita; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p06, 2024)
Micro business Loan at BRI Unit Lelateng is a goverrment program with a purpose provide capital to small and medium enterprise (SME) so that they can increase their productivity. This research aims to determine the effect of the suitability loan amount, increase business turnover and suitability repayment period on the smoothness of micro business credit repayment. The samples used is this research were 52 samples who were debtors who were in arrears with the Micro Business Loan at BRI Unit Lelateng. Sampling was carried out by using saturated sample technique, the data collected was through a survey method using questionnaire instrument. Then, the data were analyzed using multiple linear regression analysis. Based on the results of the analysis, it shows that the greater the loan amount, the better the smoothness of credit repayments. The greater the business turnover, the better the level of smoothness of credit returns and the longer the repayment period, the better the level of smoothness of credit returns.